Beer Turbidity Part 2: A Review of Raman Spectroscopy and Possible Future Use for Beer Turbidity Analysis. (1st April 2021) - Kahle, Eva-Maria; Zarnkow, Martin; Jacob, Fritz
Abstract: Beer turbidity Part 1 focused on beer turbidity, it origins and problems. Beer Turbidity Part 2 focuses on Raman spectroscopy (RS ), especially on TI-RMS (T urbidity I dentification - R aman M icro-S pectroscopy). The review provides a general overview of the physical basics, the areas of application, possible gaps, and the challenge for the use of Raman spectroscopy in beer and beverage analysis. Analysis of turbidity in beer is often limited to optical, microscopic and enzymatic analyses. This review explores in detail turbidity identification using Raman micro-spectroscopy as a way to identify beer turbidity particles and the possibility of establishing it as a future robust analysis method for beer.